Study the effect of Metronidazole Drug (MTZ) and Rhuscoriaria (Sumac) on Testicular Tissues and sperms of Male White Mice - Saad T. Rasheed; Ismael I. Hasan; Mustafa T. Khalaf (Tikrit Journal of Pure Science, 2018)
In this study, thirty adult Swiss male mice weighing with an average weight of twenty seven gram were used. The animals were housed in animal house of the college of Veterinary Medicine/ Tikrit University under normal conditions. The whole animals were divided into three groups each of ten mice, and subdivided into two periods (fourteen and twenty eight days), first group considered as control which were administered with distilled water only. The second group was treated with the metronidazole (MTZ) at a dose of 0.37 mg / mouse /day, the third group were administered with the sumac solution of 0.04 ml / mouse / day. All groups were administered orally.